Feminist Interpretations of Ludwig Wittgenstein - Baker, Nancy E.; Bhushan, Nalini; Braaten, Jane; Bradford, Judith; Churchill, Sandra W.; Cohen, Daniel; Craker, Tim; Crary, Alice; Farrell Smith, Janet; Hekman, Susan; Heyes, Cressida J.; Hoagland, Sarah Lucia; et al. (Penn State University Press, 2021)
The original essays in this volume, while written from diverse perspectives, share the common aim of building a constructive dialogue between two currents in philosophy that seem not readily allied: Wittgenstein, who urges us to bring our words back home to their ordinary uses, recognizing that it is our agreements in judgments and forms of life that ground intelligibility; and feminist theory, whose task is to articulate a radical critique of what we say, to disrupt precisely those taken-for-granted agreements in judgments and forms of life.Wittgenstein and feminist theorists are alike, however, in being unwilling or unable to ";make sense"; in the terms of the traditions from which they come, needing to rely on other means-including telling stories about everyday life-to change our ideas of what sense is and of what it is to make it.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 29. Jul 2021)
Keywords: LITERARY CRITICISM / European / German; Feminist theory; Théorie féministe